DISTRIBUTED MULTI-AGENT SYSTEMS FOR SUPPORTING COLLABORATIVE NETWORKED ENVIRONMENT - Adina-Georgeta CRETAN (Challenges of the Knowledge Society, 2019)
This paper proposes a distributed multi-agent system to model and support parallel and concurrent negotiations among organizations acting in the same industrial market. The complexity of the approach is given by the dynamic environment in which multi-attribute and multi-participant negotiations take place. The metaphor Interaction Abstract Machines (IAMs) is used to model the parallelism and the non-deterministic aspects of the negotiation processes that occur in Collaborative Networked Environment.